UV-C light irradiation enhances toxic effects of chlorpyrifos and its formulations. (15th January 2019) - Savić, Jasmina Z.; Petrović, Sandra Ž.; Leskovac, Andreja R.; Lazarević Pašti, Tamara D.; Nastasijević, Branislav J.; Tanović, Brankica B.; Gašić, Slavica M.; Vasić, Vesna M.
Highlights: UV-C irradiation of chlorpyrifos and its formulations enhances their toxic effects. Irradiated chlorpyrifos and its formulations induce DNA damage and oxidative stress. Technical chlorpyrifos is a more potent genotoxic inducer than its formulations. Irradiated chlorpyrifos formulations affect acetylcholinesterase differently. Abstract: UV-C irradiation is widely used in the food industry. However, the health effects from dietary exposure to the irradiated pesticide residues retained in foodstuffs are underestimated. In this study, technical chlorpyrifos (TCPF) and its oil in water (EW) and emulsifiable concentrate (EC) formulations were irradiated by UV-C, and their photodegradation products were subjected to toxicity assessment, including determination of acetylcholinesterase (AChE) activity, genotoxicity and oxidative stress using human blood cells as a model system. Toxicity studies were performed using the chlorpyrifos concentrations in the range of those proposed as the maximum residue levels in plant commodities. TCPF, EW and EC photodegradation products induced DNA damage and oxidative stress, and their genotoxicity did not decrease as a function of irradiation time. Irradiated TCPF and EC are more potent AChE inhibitors than irradiated EW. Accordingly, the application of UV-C irradiation must be considered when processing the plants previously treated with chlorpyrifos formulations.